TELAAH TEORETIS MODEL EXPERIENTIAL LEARNING DALAM PELATIHAN KEWIRAUSAHAAN PROGRAM PENDIDIKAN NON FORMAL - Prasetya, Iis (MAJALAH ILMIAH PEMBELAJARAN, 2011)
This paper aims to examine the model of experiential learning, theoretically, and to consider it's appropriateness to be applied in entrepreneurship training, especially in non-formal education programs. The Characteristics contained in this learning model is in accordance with the characteristics of the learner of non-formal education programs. Thus, philosophically speaking, learning experiential model is in accordance with the philosophy of non-formal education. Therefore, this accordance create the possibility of this model application in non-formal education programs, specifically those which aimed at improving or developing the entrepreneurial spirit and learner in the community.